2003
DOI: 10.1007/bf02867390
|View full text |Cite
|
Sign up to set email alerts
|

Effect of type II collagen treatment on the antioxidant status in immune tissues of adjuvant induced arthritic rats

Abstract: Adjuvant induced arthritis (AIA) is a model widely used to study Rheumatoid arthritis (RA). In the present study, lipid peroxides level in spleen and thymus of AIA rats was observed to be significantly high compared to normal rats. A significant decrease in ascorbic acid (ASA), reduced glutathione (GSH), superoxide dismutase activity (SOD) was also observed in spleen and thymus of AIA rats compared to normal rats. There was also a steady increase in the circulating immune complex level (CIC) throughout the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In groups treated with Vit C and GTE, levels of GSH elevated to reach normal levels. Low levels of GSH in RA had been reported (42). In addition, Kraus and his coworkers found that Zn-deficient rats have lowered GSH concentrations (43).…”
Section: Effect Of Green Tea Extract and Vitamin Cmentioning
confidence: 97%
“…In groups treated with Vit C and GTE, levels of GSH elevated to reach normal levels. Low levels of GSH in RA had been reported (42). In addition, Kraus and his coworkers found that Zn-deficient rats have lowered GSH concentrations (43).…”
Section: Effect Of Green Tea Extract and Vitamin Cmentioning
confidence: 97%